Filipiniana book guild series I - Philippines. National Commission for Culture and the Arts.; Filipinas Heritage Library ([Manila] National Commission for Culture and the Arts and the Filipinas Heritage Library, 2001)
Provides an image archive of all of the 24 volumes of the Filipiniana Book Guild Series I published between 1962 and 1976 in a searchable database based on the original table of contents and index of the books.
20 years in the Philippines / Paul Proust de La Gironiere (1962) -- A voyage to the Philippines / Giovanni Francesco Gemelli (1963) -- A visit to the Philippine islands / John Bowring (1963) -- The history of Sulu / Najeeb Mitry Saleeby (1963) -- A voyage to the Indian seas / Guillaume Joseph Hyacinthe Le Gentil de la Galaisiere (1964) -- The Filipino rebel / Maximo Kalaw (1964) -- Romance and adventure in old Manila / Percy A. Hill (1964) -- The colonization and conquest of the Philippines by Spain : some contemporary source documents, 1559-1577 / compiled by the Editorial Board, Filipiniana Book Guild (1965)-- Travels in the Philippines / Fedor Jagor (1965) -- An historical view of the Philippines / Joaquin Martinez de Zuniga (1966) -- Recollections of Manila and the Philippines / Robert MacMicking (1967) -- Occupied Philipines: role of Jose B. Vargas during the Japanese occupation / Armando J. Malay (1967) -- The Philippines circa 1900 : Philipine life in town & country / James A. Le Roy (1968) -- First voyage around the world / Antonio Pigafetta (1969) -- State of the Philippines in 1810 / Tomas de Comyn (1969) -- The world of Felix Roxas / Felix M. Roxas (1970) -- Luzon and Palawan / Alfred Marche (1970) -- Quezon: paladin of Philippine freedom / Carlos Quirino (1971) -- Travel accounts of the islands (1513-1787) / Tome Pires (1971) -- Christianization of the Philippines / Miguel Bernad (1972) -- Status of the Philippines in 1800 / Joaquin Martinez de Zu?iga (1973) -- German travellers on the Cordillera (1860-1890) / Carl Semper, [et al.] (1975) -- Studies in Moro history, law and religion / Najeeb M. Saleeby (1976).
Keywords: Philippines -- Literature; Philippines -- History; Philippines -- Description and travel; Philippines; Philippines -- Social life and customs